Case Report: High-Level MET Amplification as a Resistance Mechanism of ROS1-Tyrosine Kinase Inhibitors in ROS1-Rearranged Non-Small Cell Lung Cancer - Yang, Jiangping; Zhou, Ping; Yu, Min; Zhang, Yan (Frontiers in Oncology, 2021)
Background: Although C-ros oncogene 1 (ROS1) targeted therapies have demonstrated remarkable eﬃcacy in ROS1-rearranged non-small cell lung cancer (NSCLC), patients inevitably develop resistance to ROS1- tyrosine kinase inhibitors (TKIs). Commonly acquired resistance mechanisms include a second mutation of the ROS1 kinase domain and activation of bypass signaling pathways. However, MMNG HOS Transforming gene (MET) amplification has not been reported as a novel mechanism of ROS1- TKIs resistance. Case Presentation: We report a case of a 62-year-old man diagnosed with ROS1-rearranged metastatic lung adenocarcinoma, who received first-line treatment with crizotinib for 19 months. During the course of disease, the primary lung tumor was under control while the brain metastasis progressed despite the treatment with lorlatinib. The biopsy and genetic tests of the metastatic brain tumor showed a high level of MET amplification (32 copies). However, fluorescence in situ hybridization of the primary cancer showed no MET amplification, suggesting that MET amplification may be associated with an acquired resistance to ROS1-TKIs. Summary: This case suggested that MET amplification could be explored as a potential mechanism for developing ROS1-TKIs resistance. Combination treatment with highly potent and selective MET-TKIs warrants further investigations.